Cardiac Catheter Procedures During Extracorporeal Life Support: A Risk–Benefit Analysis. (January 2014) - Panda, Biswa R.; Alphonso, Nelson; Govindasamy, Maheshkumar; Anderson, Benjamin; Stocker, Christian; Karl, Tom R.
Background: Extracorporeal life support (ECLS) is a valuable tool for situations in which cardiac disease acutely threatens the life of a child. Residual anatomic lesions have a strong negative influence on survival when ECLS is used after cardiac operations. Accurate diagnostic information is essential, and although noninvasive studies are preferred (eg, echocardiography and thoracic computed tomographic angiography), they are not always logistically practical nor adequate in complex situations under the loading and nonpulsatile flow conditions of ECLS. Methods: We analyzed our experience (February 2009 to August 2012) with cardiac ECLS for 59 children. Of the 59 children, 22 (median age and weight 19.5 days and 4 kg) with advanced cardiac dysfunction had catheter studies performed during support. Results: The 22 patients had 28 studies, without major adverse events relating to the procedure or transport. Problems leading to further therapeutic procedures (catheter based seven, hybrid two, or surgical eight) were discovered in 17 of the 22 patients. For 22 catheterized patients, total time on ECLS, weaning probability, and survival to discharge were 151.6 ± 122.6 hours, 81%, and 68%, respectively, similar to that for the 37 cardiac support patients not requiring catheter studies during support ( P = 0.94, 0.37, and 0.59, respectively). Conclusion: Assuming that undiscovered anatomic and/or hemodynamic issues would have had a strong negative influence on survival, we may conclude that the risk–benefit ratio was positive and favorable. Catheter studies during ECLS are safe and should be performed expeditiously when diagnostic questions cannot be resolved by noninvasive means.